Cannibalism in Oreochromis niloticus (Linnaeus):effect of stocking density, feed quality andsubmerged macrophytes - Abdel-Tawwab, Mohsen; El-Marakby, Hany I; Ahmad, Mohammad H (Indian Journal of Fisheries, 2014)
Three experiments were conducted in glass aquaria to determine the occurrenceof cannibalism in Nile tilapia, Oreochromis niloticus fry/fingerlings combinationsin response to stocking density, artificial feeding and submerged macrophytes.Fish with average body weight of 1.2, 5.4, 10.3, 20.4 and 30.1 g/fish incombinations designed as G1, G2, G3, G4 and G5, respectively were used. Inexperiment 1,each aquarium containing 100 L freshwater was stocked with either10 or 20 fish of G1 and 5 fish of G2, G3, G4 or G5 to obtain the ratio of 2:1 or 4:1fry/fingerlings. In experiment 2, in each aquarium, 20 fry and 5 fingerlings werestocked. Fish were fed frequently to satiation with diet containing either 20%crude protein (CP) or 25% CP. In experiment 3, in each aquarium, 20 fry and 5fingerlings ratio was randomly distributed. Fish were fed frequently to satiationwith diet containing 25% CP in experiments 2 and 3. Leaf-less stem of phragmitesplant (0.7 m long and 0.5 cm diameter) was used at densities of 0, 5, 10, 20, 30and 50 stems/m2. The number of eaten fry in all experiments was observed closelyafter 6, 24, 48, 72 and 96 hours. Each treatment in all experiments wasrepresented by five replicates. The results revealed that there was an increasein the cannibalistic rate as the size difference increased, however, the biggerfish are highly cannibalistic compared with smaller ones. The number of eatenfry significantly increased as the stocking ratio increased (P